A kind of heterocyclic aramid nanofiber membrane and preparation method thereof

By introducing small molecule physical crosslinking agents into the aromatic heterocyclic diamine monomers of benzimidazole or benzooxazole, a hydrogen bond crosslinking network is constructed, and the preparation of heterocyclic aramid nanofiber membranes in electrospinning technology is solved. The poor electrostatic spinning property problem has achieved the preparation of heterocyclic aramid nanofiber membrane with high porosity and high tensile strength, which is suitable for high temperature applications.

CN116200881BActive Publication Date: 2024-12-24SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310305614.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-27
Publication Date
2024-12-24
Estimated Expiration
2043-03-27

AI Technical Summary

Technical Problem

The prior art is difficult to prepare benzimidazole or benzooxazole heterocyclic aramid nanofiber membranes with excellent mechanical properties and heat resistance through electrospinning technology, mainly due to the rigid molecular chain and strong inter-chain hydrogen of these materials. The bonding effect leads to the lack of effective topological entanglement required for electrospinning in the solution, and the electrostatic spinning is poor.

Method used

By introducing a small molecule physical crosslinking agent into the reaction of benzimidazole or benzooxazole with aromatic diacyl chloride, a hydrogen bond crosslinking network is constructed to form a spinning glue with moderate kinetic viscosity The liquid was electrospinned at a lower rotation speed using a roller receiving device, followed by treatment in alkali solution and distilled water to remove the crosslinking agent, and a high porosity heterocyclic aramid nanofiber membrane was prepared.

Benefits of technology

It has achieved continuous preparation of heterocyclic aramid nanofiber membranes with good morphology and performance, with high tensile strength and hydrophobicity, suitable for large-scale industrial production, and remain stable under high temperature conditions, and is suitable for lithium-ion batteries and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116200881B_ABST
    Figure CN116200881B_ABST
Patent Text Reader

Abstract

A heterocyclic aramid nanofiber membrane and a preparation method thereof, wherein the preparation method comprises the steps of: adding an aromatic heterocyclic diamine monomer containing benzimidazole or benzoxazole, an aromatic diamine monomer and an aromatic diacyl chloride monomer to a solvent for reaction to obtain a heterocyclic aramid solution; adding a small molecule physical cross-linking agent to the heterocyclic aramid solution, mixing evenly to obtain a spinning dope; subjecting the spinning dope to an electrostatic spinning process to obtain a nascent heterocyclic aramid nanofiber membrane oriented along the rotation direction of a drum; soaking the nascent heterocyclic aramid nanofiber membrane in an alkaline solution and distilled water respectively, taking it out, drying it at normal pressure or freeze drying it, and then annealing it to obtain a pure heterocyclic aramid nanofiber membrane. The present invention successfully uses electrostatic spinning technology to prepare a high-performance heterocyclic aramid nanofiber membrane, which has good morphology, excellent mechanical strength and thermal stability, and good hydrophobicity, and can be used in the fields of high temperature resistant diaphragms for lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of high-performance fiber materials, and in particular to a heterocyclic aramid nanofiber membrane and a preparation method thereof. Background Art

[0002] With the development of nanomaterial preparation technology, traditional poly(p-phenylene terephthalamide) (PPTA) fiber (Kevlar) can be prepared into para-aramid nanofiber dispersion by deprotonation etching. ANFs are widely used to prepare high-performance and functional materials because of their unique one-dimensional structure and retain the excellent mechanical properties and heat resistance of Kevlar fibers. Compared with the deprotonation etching method, electrospinning technology is a widely used continuous nanofiber preparation method and has the potential for industrial large-scale production. However, due to the rigid molecular chain conformation and strong interchain hydrogen bonding, PPTA can only be dissolved in strong proton acids such as concentrated sulfuric acid, methanesulfonic acid and chlorosulfonic acid. Limited by the harsh dissolution conditions of PPTA, it is difficult to directly prepare para-aramid nanofibers by electrospinning. In order to achieve the electrospinnability of para-aramid, PPTA can usually be modified by introducing a flexible structure by copolymerization or covalent grafting. Although these methods can obtain para-aramid with good electrospinnability by improving solubility, its mechanical properties will also be seriously reduced compared with PPTA. The Chinese patent application number 202111496668.6 discloses a high-strength para-aramid nanofiber membrane and a preparation method thereof. The electrospun membrane is prepared by adding a spinning aid to a deprotonated PPTA nanofiber dispersion. Since the spinning aid uses a flexible chain polymer (such as polyethylene oxide and polyvinyl pyrrolidone, etc.), the heat resistance and thermal stability of the final para-aramid nanofiber membrane are seriously reduced. Based on the above results, it can be seen that it is very challenging to develop an electrospun aramid nanofiber membrane with excellent mechanical properties and heat resistance.

[0003] Heterocyclic aramids, which are typically represented by the introduction of benzimidazole units or benzoxazole units on the basis of PPTA molecular chains, have good solubility and excellent mechanical properties. This makes them ideal materials for the preparation of high-performance electrospun aramid nanofiber membranes. However, the rigid nature of the molecular chains of these two types of heterocyclic aramids makes them lack the effective topological entanglement required for electrospinning in solution, and thus exhibit poor electrospinnability.

[0004] So far, there has been no report on the preparation of benzimidazole or benzoxazole heterocyclic aramid nanofiber membranes by electrospinning technology. How to improve the electrospinnability of these two types of heterocyclic aramid solutions by regulating the properties of the solution and obtain heterocyclic aramid nanofiber materials with reliable performance is still an important research topic. Summary of the invention

[0005] Based on this, the present invention provides a heterocyclic aramid nanofiber membrane and a preparation method thereof to solve the problem of electrostatic spinnability of benzimidazole or benzoxazole heterocyclic aramid solutions. The method successfully prepares a heterocyclic aramid nanofiber membrane with good morphology and performance. The preparation process is bottom-up, simple and easy to operate, and has the potential for industrial large-scale production.

[0006] To achieve the above object, the present invention provides a method for preparing a heterocyclic aramid nanofiber membrane, which comprises the following steps:

[0007] (1) dissolving an aromatic heterocyclic diamine monomer containing benzimidazole or benzoxazole and an aromatic diamine monomer in a solvent; and adding an aromatic diacid chloride monomer to react to obtain a heterocyclic aramid solution, wherein the molar ratio of the total amount of the aromatic heterocyclic diamine monomer and the aromatic diamine monomer to the aromatic diacid chloride monomer is 1:(0.9-1.1), and the molar proportion of the aromatic diamine monomer in the total amount of the aromatic heterocyclic diamine monomer and the aromatic diamine monomer is 0%-60%, that is, the aromatic heterocyclic diamine is the main component and the aromatic diamine is introduced as a comonomer;

[0008] (2) adding an inorganic polyacid or an organic polyacid as a small molecule physical crosslinking agent in a mass concentration of 2% to 6% to the heterocyclic aramid solution, and mixing them uniformly to obtain a spinning dope having a mass concentration of 1% to 3.0% of the heterocyclic aramid polymer and a dynamic viscosity of 1 to 20 Pa·s;

[0009] (3) subjecting the spinning dope to an electrostatic spinning process, and using a roller receiving device to collect the spun fibers at a rotation speed of 300 to 1000 rpm, to obtain a primary heterocyclic aramid nanofiber membrane oriented along the rotation direction of the roller;

[0010] (4) The nascent heterocyclic aramid nanofiber membrane is soaked in an alkaline solution and distilled water respectively, taken out, dried at normal pressure or freeze-dried, and then annealed to obtain a pure heterocyclic aramid nanofiber membrane with a diameter of 120 to 400 nm.

[0011] In step (4), the porosity of the heterocyclic aramid nanofiber membrane obtained by normal pressure drying is 20% to 40%, the tensile strength along the orientation direction is 400 to 600 MPa, and the tensile strength in the direction perpendicular to the orientation direction is 40 to 60 MPa; the porosity of the heterocyclic aramid nanofiber membrane obtained by freeze drying is 80% to 95%, the water contact angle is 105° to 120°, the tensile strength along the orientation direction is 80 to 150 MPa, and the tensile strength in the direction perpendicular to the orientation direction is 10 to 20 MPa.

[0012] As a further preferred technical solution of the present invention, in step (1), the solvent used is a composite solvent composed of a polar aprotic organic solvent and an inorganic salt co-solvent, and the mass concentration of the inorganic salt co-solvent in the polar aprotic organic solvent is 1% to 9%; the polar aprotic organic solvent includes: one or more of N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and N-methylpyrrolidone (NMP); the inorganic salt co-solvent includes: one or more of lithium chloride (LiCl), calcium chloride (CaCl2), lithium bromide (LiBr), and calcium bromide (CaBr2).

[0013] As a further preferred technical solution of the present invention, the reaction in step (1) is carried out under the protection of inert gas. During the reaction, the aromatic heterocyclic diamine monomer containing benzimidazole or benzoxazole and the aromatic diamine monomer are first added to the solvent, and then the aromatic diacyl chloride monomer is added in two stages for reaction: in the first stage, 70% to 90% of the amount of the aromatic diacyl chloride monomer is added and reacted at 0 to 5° C. for 20 to 40 minutes; in the second stage, the remaining aromatic diacyl chloride monomer is added and reacted at 20 to 40° C. for 1 to 2 hours. The mass concentration of the obtained heterocyclic aramid solution is 3% to 7%, the dynamic viscosity at room temperature is 300 to 1200 Pa·s, and the intrinsic viscosity is 10 to 20 dL / g. After the diamine monomer is dissolved, the water content in the solution should be controlled to be ≤100 ppm to prevent the diacyl chloride monomer from reacting with water and being inactivated, resulting in too low intrinsic viscosity of the heterocyclic aramid.

[0014] As a further preferred technical solution of the present invention, the heterocyclic aramid obtained by polymerization in step (1) has good solubility in the composite solvent, and the appearance of the heterocyclic aramid solution obtained by polymerization is uniform and isotropic. There should be no gelation or precipitation of the heterocyclic aramid solution due to poor solubility of the heterocyclic aramid. Based on the solubility of the heterocyclic aramid, in step (1):

[0015] The aromatic heterocyclic diamine monomer is selected from: one or more of 2-(4-aminophenyl)-5-aminobenzoxazole (PBOA), 2-(3-aminophenyl)-5-aminobenzoxazole (MBOA), 2-(4-aminophenyl)-5-aminobenzimidazole (PABZ), 2-(3-aminophenyl)-5-aminobenzimidazole (MABZ), and 2-2'-p-phenyl-bis-benzimidazole diamine (BPABZ), wherein the structural formula of each monomer is specifically shown in Table 1.

[0016] Table 1

[0017]

[0018] The aromatic diamine monomer is selected from: (1) phenyl type: p-phenylenediamine (PDA), 2-chloro-4-aminoaniline (PDA-Cl); (2) biphenyl type: 4,4'-benzenediamine (HPA), 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB), 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl (THMB); (3) phenyl spacer type: one or more of 4,4'-diaminobenzanilide (DABA), 4,4'-diaminodiphenyl ether (4,4'-ODA), and p-aminophenyl para-aminobenzoate (APAB), wherein the structural formula of each monomer is specifically shown in Table 2.

[0019] Table 2

[0020]

[0021]

[0022] The aromatic diacyl chloride monomer is selected from one or more of terephthaloyl chloride (TPC), isophthaloyl chloride (IPC), 4,4'-benzil chloride (BPC), and 4,4'-diphenyl ether dichloride (DEDC), wherein the structural formula of each monomer is specifically shown in Table 3.

[0023] Table 3

[0024]

[0025] As a further preferred technical solution of the present invention, the small molecule physical crosslinking agent is a polybasic organic acid or inorganic acid such as sulfuric acid, oxalic acid, phosphoric acid, polyphosphoric acid, etc. The spinning dope obtained in step (2) contains a heterocyclic aramid polymer with a mass concentration of 1% to 3.0%, and the dynamic viscosity of the spinning dope is in the range of 1 to 20 Pa·s. In actual production, if the viscosity of the spinning dope is too high or too low, it is not conducive to the stability and continuity of the heterocyclic aramid nanofiber molding and the electrospinning process.

[0026] As a further preferred technical solution of the present invention, the electrospinning process conditions in step (3) are: voltage 18-30 kV, spinning rate 0.1-3 mL / h, distance between the needle and the roller receiving device 5-30 cm, temperature 20-50° C., relative humidity 30-50%. Using the roller receiving device at a speed of 300-1000 rpm, a heterocyclic aramid nanofiber membrane oriented along the rotation direction of the roller can be obtained. If a flat plate receiving device is used, the nanofibers stand vertically on the flat plate receiving device, and a heterocyclic aramid nanofiber membrane cannot be obtained.

[0027] As a further preferred technical solution of the present invention, in step (4), the alkaline solution is an aqueous solution of an alkaline substance, the alkaline substance is an organic base or an inorganic base, and the pH value of the alkaline solution is 8 to 11; the soaking temperature is 20 to 80°C, and the time is 1 to 24 hours; the normal pressure drying temperature is 50 to 100°C, and the time is 1 to 5 hours; the annealing temperature is 360 to 410°C, and the time is 0.5 to 1 hour.

[0028] According to another aspect of the present invention, the present invention further provides a heterocyclic aramid nanofiber membrane manufactured by any of the above-mentioned methods for preparing heterocyclic aramid nanofiber membranes.

[0029] The heterocyclic aramid nanofiber membrane and the preparation method thereof of the present invention can achieve the following by adopting the above technical scheme:

[0030] Beneficial effects:

[0031] 1. The present invention realizes the preparation of continuous heterocyclic aramid nanofiber membrane by electrospinning technology for the first time. By adding a small molecule physical crosslinker to construct a hydrogen bond crosslinking network between rigid heterocyclic aramid molecular chains to achieve the topological entanglement of the molecular chains required for electrospinning, the small molecule physical crosslinker can be removed by washing with alkaline solution and distilled water after the nanofiber is formed to obtain a pure heterocyclic aramid nanofiber membrane.

[0032] 2. The primary heterocyclic aramid nanofiber membrane provided by the present invention exhibits good hydrophilicity due to the presence of a large amount of inorganic salt cosolvents and small molecule physical crosslinkers, which enables it to be transformed into a heterocyclic aramid nanofiber hydrogel during immersion in an alkaline solution and distilled water, and a high-porosity heterocyclic aramid nanofiber membrane is further prepared by freeze-drying or supercritical drying technology.

[0033] 3. The spinning dope prepared by the present invention does not require a special receiving device during the electrospinning process. Only a roller receiving device is required at a relatively low rotation speed (300 rpm) to obtain a heterocyclic aramid nanofiber membrane having a high degree of orientation along the rotation direction of the roller.

[0034] 4. The heterocyclic aramid nanofiber membrane provided by the present invention has a water contact angle of 105° to 120° and has good hydrophobicity; it has excellent thermal stability and high tensile strength due to the high orientation of the heterocyclic aramid nanofibers, and can be used in the fields of high temperature resistant diaphragms for lithium ion batteries.

[0035] 5. The preparation process of the heterocyclic aramid nanofiber membrane of the present invention adopts a bottom-up synthesis preparation strategy, which is simple and easy to operate and suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0037] Figure 1 This is the heterocyclic aramid nanofiber membrane prepared in Example 1.

[0038] Figure 2 These are the stretching curves of the heterocyclic aramid nanofiber membrane prepared in Example 1 along the directions parallel to the orientation direction and perpendicular to the orientation direction.

[0039] Figure 3 The SEM surface and cross-sectional morphologies of the freeze-dried heterocyclic aramid nanofiber hydrogel prepared in Example 2.

[0040] Figure 4 This is a water contact angle test diagram of the heterocyclic aramid nanofiber membrane prepared in Example 2.

[0041] Figure 5 This is the thermal gravimetric curve of the heterocyclic aramid nanofiber membrane prepared in Example 3 under N2 atmosphere.

[0042] Figure 6 Surface and cross-sectional SEM images of the heterocyclic aramid nanofiber membrane prepared in Example 4.

[0043] Figure 7 These are the stretching curves of the heterocyclic aramid nanofiber membrane prepared in Example 4 along the directions parallel to the orientation direction and perpendicular to the orientation direction.

[0044] Figure 8 This is a water contact angle test diagram of the heterocyclic aramid nanofiber membrane prepared in Example 4.

[0045] Fig. 9 This is the morphology of the nanofibers collected after electrospinning of the heterocyclic aramid spinning dope in Comparative Example 1 without adding a small molecule physical cross-linking agent.

[0046] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0047] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0048] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0049] The premise for the realization of the present invention is that the heterocyclic aramid obtained by polymerization has good solubility in the listed composite solvents, and can form a uniform isotropic heterocyclic aramid solution. If gelation or precipitation occurs during the polymerization process due to the poor solubility of the heterocyclic aramid, it is not conducive to the preparation of heterocyclic aramid nanofiber membranes by electrostatic spinning technology. On this basis, adding a small molecule physical crosslinker with a mass concentration of 2% to 6% to the uniform isotropic heterocyclic aramid solution can significantly improve its electrostatic spinnability. The five aromatic heterocyclic diamine monomers listed in Table 1 can react with the three aromatic diacid chloride monomers listed in Table 3 to form heterocyclic aramid with good solubility. On this basis, one or more of the listed phenyl-type, biphenyl-type or phenyl-interval-type aromatic diamine monomers are introduced in the form of copolymerization, and the molar proportion of the aromatic heterocyclic diamine monomer and the aromatic diamine monomer is controlled to be 0% to 60%, and a uniform isotropic heterocyclic aramid solution can be obtained by polymerization.

[0050] Example 1

[0051] (1) Using BPABZ and TPC as raw materials, 6.61 g of BPABZ was dissolved in 200 g of DMAc / LiCl composite solvent (LiCl mass concentration was 4%) at room temperature under N2 atmosphere. After the diamine monomer was dissolved, the temperature was lowered to 2°C, and the water content was 80 ppm. Then 3.92 g of TPC was added twice, with a time interval of 30 min. The molar ratio of diamine to diacyl chloride was 1:1. After the last addition of TPC, the temperature was raised to 35°C and stirred for 1 h, and finally a heterocyclic aramid solution with a mass concentration of 4.33% and an intrinsic viscosity of 15.4 dL / g was obtained.

[0052] (2) 242.9 g DMAc and 14.3 g concentrated sulfuric acid were mixed uniformly in an ice-water bath, and then slowly added into 100 g heterocyclic aramid rubber solution using a constant pressure funnel. After continuous stirring for 1 h under ice-water cooling conditions, a uniform spinning dope with a heterocyclic aramid content of 1.21% and a sulfuric acid content of 4.0% was obtained.

[0053] (3) Add an appropriate amount of the above spinning solution into a 5 mL syringe with a diameter of 12.5 mm, and use a 23G flat-tip needle for electrospinning. The parameters are set as follows: voltage 23 kV, spinning speed 3.0 mL / h, distance between the needle and the roller receiving device 8 cm, roller speed 300 rpm, temperature 30 ° C, relative humidity 42%. Set the spinning time to 4 h, and finally obtain a primary heterocyclic aramid nanofiber membrane oriented along the rotation direction of the roller.

[0054] (4) The obtained nascent heterocyclic aramid nanofibers were immersed in a 2.5% ammonia solution at room temperature for 6 hours, and then transferred to distilled water for 24 hours, with the water changed three times in the middle, to obtain heterocyclic aramid nanofiber hydrogel.

[0055] (5) The obtained heterocyclic aramid nanofiber hydrogel was dried in a forced air oven at 80°C for 10 h. Finally, the dried membrane was thermally annealed at 380°C for 0.5 h to obtain a heterocyclic aramid nanofiber membrane.

[0056] Figure 1 The obtained light yellow translucent heterocyclic aramid nanofiber membrane has a thickness of about 10 μm and a porosity of 26%. Figure 2 (a) and (b) are the tensile curves of the heterocyclic aramid nanofibers parallel to the orientation direction and perpendicular to the orientation direction after thermal annealing, respectively. The tensile strength along the direction parallel to the orientation direction is as high as 576MPa. Although the tensile strength perpendicular to the orientation direction is only 45.4MPa, it is still higher than most electrospun membranes. The difference in mechanical properties of the heterocyclic aramid nanofiber membrane in different directions also indicates that the heterocyclic aramid nanofibers are oriented along the direction of the drum rotation.

[0057] Example 2

[0058] (1) With PABZ and TPC as raw materials, 13.8g PABZ was dissolved in 500g DMAc / LiCl composite solvent (LiCl mass concentration was 3.5%) at room temperature under N2 atmosphere. After the diamine monomer was dissolved, the temperature was lowered to 2°C, and the water content was 80ppm. Then 12.4g TPC was added twice, with a time interval of 20min. The molar ratio of diamine to diacyl chloride was 1:0.99. After the last addition of TPC, the temperature was raised to 35°C and stirred for 1h, and finally a heterocyclic aramid solution with a mass concentration of 4.15% and an intrinsic viscosity of 13.1dL / g was obtained.

[0059] (2) 29.2 g DMAc and 4.17 g concentrated sulfuric acid were mixed evenly in an ice-water bath, and then slowly added into 50 g heterocyclic aramid rubber solution using a constant pressure funnel. After continuous stirring for 1 h under ice-water cooling conditions, a uniform spinning dope with a heterocyclic aramid content of 2.5% and a sulfuric acid content of 5.0% was obtained.

[0060] (3) Add an appropriate amount of the above spinning solution into a 5mL syringe with a diameter of 12.5mm, and use a 23G flat-tip needle for electrospinning. The parameters are set as follows: voltage 25kV, spinning speed 1.5mL / h, distance between the needle and the roller receiving device 10cm, roller speed 500rpm, temperature 28℃, relative humidity 40%. Set the spinning time to 6h, and finally obtain a primary heterocyclic aramid nanofiber membrane oriented along the rotation direction of the roller.

[0061] (4) The obtained nascent heterocyclic aramid nanofibers were immersed in a 3% ammonia solution at room temperature for 6 hours, and then transferred to distilled water for 24 hours, with the water changed three times in the middle, to obtain heterocyclic aramid nanofiber hydrogel.

[0062] (5) freeze-drying the obtained heterocyclic aramid nanofiber hydrogel. Finally, the dried membrane was thermally annealed at 380° C. for 0.5 h to obtain a heterocyclic aramid nanofiber membrane with a porosity of 94%.

[0063] Figure 3 The surface and cross-section SEM images of the freeze-dried heterocyclic aramid nanofiber hydrogel are shown in Figure 2. The high porosity and loose cross-section morphology indicate that the heterocyclic aramid nanofiber hydrogel was obtained after alkali washing and water washing. Figure 4 This is the water contact angle test result of the obtained heterocyclic aramid nanofiber membrane. It can be seen that it exhibits hydrophobicity and the water contact angle is about 114°.

[0064] Example 3

[0065] (1) With PBOA, PDA and TPC as raw materials, 2.92g PBOA and 1.40g PDA were dissolved in 150g DMAc / LiCl composite solvent (LiCl mass concentration was 3.5%, diamine monomer molar ratio BOA:PDA=1:1) at room temperature under N2 atmosphere. After the diamine monomer was dissolved, the temperature was lowered to 3°C, and the water content was 100ppm. Then 5.26g TPC was added twice, with a time interval of 30min, and the molar ratio of diamine to diacyl chloride was 1:1. After the last addition of TPC, the temperature was raised to 30°C and stirred for 1h, and finally a heterocyclic aramid solution with a mass concentration of 4.81% and an intrinsic viscosity of 13.5dL / g was obtained.

[0066] (2) 62.3 g DMAc and 3.43 g concentrated sulfuric acid were mixed evenly in an ice-water bath, and then slowly added into 20 g heterocyclic aramid rubber solution using a constant pressure funnel. After continuous stirring for 1.0 h under ice-water cooling conditions, a uniform spinning dope with a heterocyclic aramid content of 1.12% and a sulfuric acid content of 4% was obtained.

[0067] (3) Add an appropriate amount of the above spinning solution into a 5mL syringe with a diameter of 12.5mm, and use a 25G flat-tip needle for electrospinning. The parameters are set as follows: voltage 23kV, spinning speed 2.0mL / h, distance between the needle and the roller receiving device 8cm, roller speed 500rpm, temperature 32℃, relative humidity 45%. Set the spinning time to 5h, and finally obtain a primary heterocyclic aramid nanofiber membrane oriented along the rotation direction of the roller.

[0068] (4) The obtained nascent heterocyclic aramid nanofibers were immersed in a 1.5% KOH aqueous solution at room temperature for 6 hours, and then transferred to distilled water for 24 hours, with the water changed three times in the middle, to obtain heterocyclic aramid nanofiber hydrogel.

[0069] (5) The obtained heterocyclic aramid nanofiber hydrogel was dried in a forced air oven at 80° C. for 10 h. Finally, the dried membrane was thermally annealed at 360° C. for 0.5 h to obtain a heterocyclic aramid nanofiber membrane with a porosity of 31.5%.

[0070] Figure 5 This is the thermal weight loss curve of the obtained heterocyclic aramid nanofiber membrane. Thermal weight loss does not begin until 505°C, indicating that the heterocyclic aramid nanofiber membrane has good thermal stability.

[0071] Example 4

[0072] (1) With PABZ, PDA and TPC as raw materials, 3.20g PABZ and 1.54g PDA were dissolved in 200g DMAc / LiCl composite solvent (LiCl mass concentration was 3.5%, diamine monomer molar ratio PABZ:PDA=1:1) at room temperature under N2 atmosphere. After the diamine monomer was dissolved, the temperature was lowered to 5°C, and the water content was 50ppm. Then 5.78g TPC was added twice, with a time interval of 20min. The molar ratio of diamine to diacyl chloride was 1:0.998. After the last addition of TPC, the temperature was raised to 35°C and stirred for 1h, and finally a heterocyclic aramid solution with a mass concentration of 4.01% and an intrinsic viscosity of 15.2dl / g was obtained.

[0073] (2) 73.4 g DMAc and 3.75 g concentrated sulfuric acid were mixed evenly in an ice-water bath, and then slowly added into 30 g heterocyclic aramid rubber solution using a constant pressure funnel. After continuous stirring for 1 h under ice-water cooling conditions, a uniform spinning dope with a heterocyclic aramid content of 1.12% and a sulfuric acid content of 3.5% was obtained.

[0074] (3) Add an appropriate amount of the above spinning solution into a 5mL syringe with a diameter of 12.5mm, and use a 25G flat-tip needle for electrospinning. The parameters are set as follows: voltage 22kV, spinning speed 1.0mL / h, distance between the needle and the roller receiving device 10cm, roller speed 300rpm, temperature 30℃, relative humidity 45%. Set the spinning time to 10h, and finally obtain a primary heterocyclic aramid nanofiber membrane oriented along the rotation direction of the roller.

[0075] (4) The obtained nascent heterocyclic aramid nanofibers were immersed in a 1.5% NaOH aqueous solution at room temperature for 6 hours, and then transferred to distilled water for 24 hours, with the water changed three times in the middle, to obtain heterocyclic aramid nanofiber hydrogel.

[0076] (5) The obtained heterocyclic aramid nanofiber hydrogel was dried in a forced air oven at 80° C. for 10 h. Finally, the dried membrane was thermally annealed at 360° C. for 0.5 h to obtain a heterocyclic aramid nanofiber membrane with a porosity of 31%.

[0077] Figure 6 (a) and (b) are the surface and cross-sectional SEM images of the heterocyclic aramid nanofiber membrane collected by a roller in Example 2. It can be seen that the heterocyclic aramid nanofiber has a smooth morphology and a uniform diameter distribution. Figure 6 (a) It can be seen that the heterocyclic aramid nanofibers have obvious orientation. Figure 7 (a) and (b) are the tensile curves of the heterocyclic aramid nanofibers parallel to the orientation direction and perpendicular to the orientation direction after thermal annealing, respectively. The tensile strength parallel to the orientation direction is as high as 510MPa. Although the tensile strength perpendicular to the orientation direction is only 50MPa, it is still higher than most electrospun membranes. Figure 8 This is the water contact angle test result of the obtained heterocyclic aramid nanofiber membrane. It can be seen that it exhibits hydrophobicity and the water contact angle is about 106°.

[0078] Example 5

[0079] (1) With PABZ, TFMB and TPC as raw materials, 3.47g PABZ and 4.96g TFMB were dissolved in 280g DMAc / LiCl composite solvent (LiCl mass concentration was 3.0%, diamine monomer molar ratio PABZ:TFMB=1:1) at room temperature under argon atmosphere. After the diamine monomer was dissolved, the temperature was lowered to 0°C, and the water content was 95ppm. Then 6.30g TPC was added twice, with a time interval of 40min. The molar ratio of diamine to diacyl chloride was 1:1. After the last addition of TPC, the temperature was raised to 40°C and stirred for 2h, and finally a heterocyclic aramid solution with a mass concentration of 4.23% and an intrinsic viscosity of 14.1dL / g was obtained.

[0080] (2) 52.7 DMAc and 6.88 g of concentrated sulfuric acid were mixed evenly in an ice-water bath, and then slowly added into 55 g of heterocyclic aramid rubber solution using a constant pressure funnel. After continuous stirring for 2 h under ice-water cooling conditions, a uniform spinning dope with a heterocyclic aramid content of 2.0% and a sulfuric acid content of 6.0% was obtained.

[0081] (3) Add an appropriate amount of the above spinning solution into a 5mL syringe with a diameter of 12.5mm, and use a 22G flat-tip needle for electrospinning. The parameters are set as follows: voltage 28kV, spinning speed 0.5mL / h, distance between the needle and the roller receiving device 12cm, roller speed 400rpm, temperature 29℃, relative humidity 43%. Set the spinning time to 20h, and finally obtain a primary heterocyclic aramid nanofiber membrane oriented along the rotation direction of the roller.

[0082] (4) The obtained nascent heterocyclic aramid nanofibers were immersed in a 5% Na2CO3 aqueous solution at room temperature for 12 hours, and then transferred to distilled water for 24 hours, with the water changed three times in the middle, to obtain heterocyclic aramid nanofiber hydrogel.

[0083] (5) The obtained heterocyclic aramid nanofiber hydrogel was dried in a forced air oven at 80° C. for 10 h. Finally, the dried membrane was thermally annealed at 360° C. for 0.5 h to obtain a heterocyclic aramid nanofiber membrane with a porosity of 32%.

[0084] Example 6

[0085] (1) Using MBOA, HPA and DEDC as raw materials, 2.02g MBOA and 1.65g HPA were dissolved in 170g DMAc / LiCl composite solvent (LiCl mass concentration was 3.5%) at room temperature under N2 atmosphere. After the diamine monomer was dissolved, the temperature was lowered to 3°C, and the water content was 40ppm. Then 5.26g DEDC was added twice, with a time interval of 30min. The molar ratio of diamine to diacyl chloride was 1:0.995. After the last addition of TPC, the temperature was raised to 35°C and stirred for 1h, and finally a heterocyclic aramid solution with a mass concentration of 4.27% and an intrinsic viscosity of 16.1dL / g was obtained.

[0086] (2) 104.3 g DMAc and 8.51 g concentrated sulfuric acid were mixed evenly in an ice-water bath, and then slowly added into 100 g heterocyclic aramid rubber solution using a constant pressure funnel. After continuous stirring for 1 h under ice-water cooling conditions, a uniform spinning dope with a heterocyclic aramid content of 2.0% and a sulfuric acid content of 4% was obtained.

[0087] (3) Add an appropriate amount of the above spinning solution into a 5mL syringe with a diameter of 12.5mm, and use a 25G flat-tip needle for electrospinning. The parameters are set as follows: voltage 22kV, spinning speed 1.0mL / h, distance between the needle and the roller receiving device 10cm, roller speed 300rpm, temperature 28℃, relative humidity 32%. Set the spinning time to 10h, and finally obtain a primary heterocyclic aramid nanofiber membrane oriented along the rotation direction of the roller.

[0088] (4) The obtained nascent heterocyclic aramid nanofibers were immersed in a 1.5% NaOH aqueous solution at room temperature for 6 hours, and then transferred to distilled water for 24 hours, with the water changed three times in the middle, to obtain heterocyclic aramid nanofiber hydrogel.

[0089] (5) The obtained heterocyclic aramid nanofiber hydrogel was dried in a forced air oven at 80° C. for 10 h. Finally, the dried membrane was thermally annealed at 390° C. for 1.0 h to obtain a heterocyclic aramid nanofiber membrane with a porosity of 28.5%.

[0090] Example 7

[0091] (1) Using BPABZ, 4,4'-ODA and BPC as raw materials, 2.66g BPABZ and 3.63g 4,4'-ODA were dissolved in 325g DMAc / LiCl composite solvent (LiCl mass concentration was 4.0%, diamine monomer molar ratio 4,4'-ODA:BPABZ=7:3) at room temperature under argon atmosphere. After the diamine monomer was dissolved, the temperature was lowered to 0°C, and the water content was 30ppm. Then 7.24g BPC was added twice, with a time interval of 45min. The molar ratio of diamine to diacyl chloride was 1:1. After the last addition of BPC, the temperature was raised to 40°C and stirred for 1h, and finally a heterocyclic aramid solution with a mass concentration of 3.44% and an intrinsic viscosity of 18.6dL / g was obtained.

[0092] (2) 142.8 DMAc and 4.14 g polyphosphoric acid were mixed evenly in an ice-water bath, and then slowly added into 60 g heterocyclic aramid rubber solution using a constant pressure funnel. After continuous stirring for 2 h under ice-water cooling conditions, a uniform spinning dope with a heterocyclic aramid content of 1.0% and a polyphosphoric acid content of 2.0% was obtained.

[0093] (3) Add an appropriate amount of the above spinning solution into a 5mL syringe with a diameter of 12.5mm, and use a 25G flat-tip needle for electrospinning. The parameters are set as follows: voltage 28kV, spinning speed 1.5mL / h, distance between the needle and the roller receiving device 10cm, roller speed 400rpm, temperature 27.5℃, relative humidity 46%. Set the spinning time to 8h, and finally obtain a primary heterocyclic aramid nanofiber membrane oriented along the rotation direction of the roller.

[0094] (4) The obtained nascent heterocyclic aramid nanofibers were immersed in a 1.5% LiOH aqueous solution at room temperature for 6 hours, and then transferred to distilled water for 24 hours, with the water changed three times in the middle, to obtain heterocyclic aramid nanofiber hydrogel.

[0095] (5) The obtained heterocyclic aramid nanofiber hydrogel was dried in a forced air oven at 80° C. for 10 h. Finally, the dried membrane was thermally annealed at 360° C. for 0.5 h to obtain a heterocyclic aramid nanofiber membrane with a porosity of 30.8%.

[0096] Example 8

[0097] (1) With MABZ, DABA and TPC as raw materials, 2.75g MABZ and 2.79g DABA were dissolved in 200g DMAc / LiCl composite solvent (LiCl mass concentration was 3.5%, diamine monomer molar ratio DABA:MABZ=1:1) at room temperature under N2 atmosphere. After the diamine monomer was dissolved, the temperature was lowered to 5°C, and the water content was 100ppm. Then 4.95g TPC was added twice, with a time interval of 50min. The molar ratio of diamine to diacyl chloride was 1:0.992. After the last addition of TPC, the temperature was raised to 35°C and stirred for 1h, and finally a heterocyclic aramid solution with a mass concentration of 4.15% and an intrinsic viscosity of 12.5dL / g was obtained.

[0098] (2) 115.0 g DMAc and 5.0 g anhydrous oxalic acid were mixed evenly, and then slowly added into 80 g heterocyclic aramid rubber solution using a constant pressure funnel. After continuous stirring for 2 h under ice-water cooling conditions, a uniform spinning dope with a heterocyclic aramid content of 1.66% and an oxalic acid content of 2.5% was obtained.

[0099] (3) Add an appropriate amount of the above spinning solution into a 5mL syringe with a diameter of 12.5mm, and use a 25G flat-tip needle for electrospinning. The parameters are set as follows: voltage 25kV, spinning speed 2.0mL / h, distance between the needle and the roller receiving device 8cm, roller speed 500rpm, temperature 32℃, relative humidity 46%. Set the spinning time to 5h, and finally obtain a primary heterocyclic aramid nanofiber membrane oriented along the rotation direction of the roller.

[0100] (4) The obtained nascent heterocyclic aramid nanofibers were immersed in a 1.5% NaOH aqueous solution at room temperature for 6 hours, and then transferred to distilled water for 24 hours, with the water changed three times in the middle, to obtain heterocyclic aramid nanofiber hydrogel.

[0101] (5) The obtained heterocyclic aramid nanofiber hydrogel was dried in a forced air oven at 80° C. for 10 h. Finally, the dried membrane was thermally annealed at 400° C. for 0.5 h to obtain a heterocyclic aramid nanofiber membrane with a porosity of 36%.

[0102] Example 9

[0103] The heterocyclic aramid nanofiber membrane was prepared using the same process parameters and method as in Example 1, except that:

[0104] In step (1), the heterocyclic aramid solution obtained by polymerization with PBOA and TPC as raw materials has a mass concentration of 4.15% and an intrinsic viscosity of 15.2 dL / g. The thickness of the heterocyclic aramid nanofiber membrane finally obtained is about 10 μm, the porosity is 28.5%, the tensile strength along the direction parallel to the orientation is as high as 465 MPa, and the tensile strength perpendicular to the orientation direction is 45.4 MPa.

[0105] Example 10

[0106] The heterocyclic aramid nanofiber membrane was prepared using the same process parameters and method as in Example 1, except that:

[0107] In step (1), BPABZ and DEDC were used as raw materials, and the mass concentration of the obtained heterocyclic aramid solution was 4.43%, and the intrinsic viscosity was 14.5 dL / g. The thickness of the heterocyclic aramid nanofiber membrane finally obtained was about 10 μm, the porosity was 35%, the tensile strength along the direction parallel to the orientation was as high as 420 MPa, and the tensile strength perpendicular to the orientation was 40.4 MPa.

[0108] Embodiment 11

[0109] The heterocyclic aramid nanofiber membrane was prepared using the same process parameters and method as in Example 3, except that:

[0110] In step (1), PBOA, 4,4'-ODA and TPC were used as raw materials, and the heterocyclic aramid solution obtained by polymerization had a mass concentration of 4.95% and an intrinsic viscosity of 14.9 dL / g. The thermal decomposition temperature of the heterocyclic aramid nanofiber membrane finally obtained was 495°C.

[0111] Example 12

[0112] The heterocyclic aramid nanofiber membrane was prepared using the same process parameters and method as in Example 4, except that:

[0113] In step (5), the obtained heterocyclic aramid nanofiber hydrogel is freeze-dried to finally obtain a heterocyclic aramid nanofiber membrane with a porosity of 95% and a water contact angle of 114°.

[0114] Embodiment 13

[0115] The heterocyclic aramid nanofiber membrane was prepared using the same process parameters and method as in Example 5, except that:

[0116] In step (5), the obtained heterocyclic aramid nanofiber hydrogel is freeze-dried to finally obtain a heterocyclic aramid nanofiber membrane with a porosity of 93.8% and a water contact angle of 120°.

[0117] Comparative Example 1 (as a comparative experiment of Example 3, without adding a small molecule physical cross-linking agent)

[0118] The heterocyclic aramid solution was prepared by referring to the method of Example 3. The difference is that:

[0119] In step (2), 164.3 g of DMAc was slowly added into 50 g of heterocyclic aramid rubber solution using a constant pressure funnel. After continuous stirring for 2 h, a uniform spinning dope with a heterocyclic aramid mass content of 1.12% and no small molecule physical crosslinking agent was obtained.

[0120] Then, electrospinning was carried out under the same conditions as in Example 3.

[0121] Fig. 9 The morphology of the nanofibers collected after electrospinning of the heterocyclic aramid spinning dope without the addition of small molecule physical crosslinking agent. It can be seen that the above electrospinning process is discontinuous and unstable, and is accompanied by the dripping of the spinning dope.

[0122] Comparative Example 2 (as a comparative experiment of Example 4, the mismatch in the amount of small molecule physical cross-linking agent added resulted in excessive viscosity of the spinning dope)

[0123] The heterocyclic aramid solution was prepared by referring to the method of Example 4. The difference is:

[0124] In step (2), 125.9 g DMAc and 2.68 g concentrated sulfuric acid were mixed uniformly in an ice-water bath, and then slowly added to 50 g heterocyclic aramid resin solution using a constant pressure funnel. After continuous stirring for 1 hour, a uniform spinning resin solution with a heterocyclic aramid mass content of 1.12% and a sulfuric acid content of 1.5% was obtained. At this time, the apparent viscosity of the spinning resin solution was as high as 96.0 Pa·s, and the fluidity was very poor, and electrospinning could not be performed under the same conditions as in Example 4.

[0125] Comparative Example 3 (as a comparative experiment of Example 2)

[0126] The heterocyclic aramid solution was prepared by referring to the method of Example 2. The difference is that:

[0127] Step (1) was not carried out under the protection of inert gas. After the diamine was dissolved, the water content was 500 ppm and the intrinsic viscosity of the obtained hybrid aramid was 8.2 dL / g.

[0128] A uniform spinning dope having a heterocyclic aramid content of 2.5% and a sulfuric acid content of 5.0% was prepared in the same manner as in Example 2.

[0129] Then, electrospinning was performed using the same parameters as in Example 2. However, due to the low molecular weight of the heterocyclic aramid, the electrospinning process was discontinuous and unstable, and was accompanied by dripping of the spinning dope, so that a heterocyclic aramid nanofiber membrane with a good morphology and structure could not be obtained.

[0130] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A method for preparing a heterocyclic aramid nanofiber membrane, characterized in that: The following steps are involved: (1) dissolving an aromatic heterocyclic diamine monomer containing benzimidazole or benzoxazole and an aromatic diamine monomer in a solvent, and adding an aromatic diacid chloride monomer to react to obtain a heterocyclic aramid solution; wherein the molar ratio of the total amount of the aromatic heterocyclic diamine monomer and the aromatic diamine monomer to the aromatic diacid chloride monomer is 1:(0.9-1.1), and the molar proportion of the aromatic diamine monomer in the total amount of the aromatic heterocyclic diamine monomer and the aromatic diamine monomer is 0%-60%; (2) adding an inorganic polyacid or an organic polyacid as a small molecule physical crosslinking agent in a mass concentration of 2% to 6% to the heterocyclic aramid solution, and mixing them uniformly to obtain a spinning dope having a mass concentration of 1% to 3.0% of the heterocyclic aramid polymer and a dynamic viscosity of 1 to 20 Pa·s; (3) subjecting the spinning dope to an electrostatic spinning process, and using a roller receiving device to collect the spun fibers at a rotation speed of 300 to 1000 rpm, to obtain a primary heterocyclic aramid nanofiber membrane oriented along the rotation direction of the roller; (4) soaking the nascent heterocyclic aramid nanofiber membrane in an alkaline solution and distilled water respectively, taking it out, drying it at normal pressure or freeze-drying it, and then annealing it to obtain a pure heterocyclic aramid nanofiber membrane; The aromatic heterocyclic diamine monomer containing benzimidazole or benzoxazole is selected from: one or more of 2-(4-aminophenyl)-5-aminobenzoxazole, 2-(3-aminophenyl)-5-aminobenzoxazole, 2-(4-aminophenyl)-5-aminobenzimidazole, 2-(3-aminophenyl)-5-aminobenzimidazole, and 2-2'-p-phenyl-bis-benzimidazole diamine; The aromatic diamine monomer is selected from the group consisting of p-phenylenediamine, 2-chloro-4-aminoaniline, 4,4'-biphenylenediamine, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl, 4,4'-diaminobenzanilide, 4,4'-diaminodiphenyl ether, and p-aminophenyl para-aminobenzoate; The aromatic diacid chloride monomer is selected from one or more of terephthaloyl chloride, isophthaloyl chloride, 4,4'-benzil chloride, and 4,4'-diacid diphenyl ether.

2. The method for preparing the heterocyclic aramid nanofiber membrane according to claim 1, characterized in that: In step (1), the solvent used is a composite solvent prepared from a polar aprotic organic solvent and an inorganic salt co-solvent, and the mass concentration of the inorganic salt co-solvent in the polar aprotic organic solvent is 1% to 9%; The polar aprotic organic solvent includes: one or more of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; The inorganic salt co-solvent includes: one or more of lithium chloride, calcium chloride, lithium bromide, and calcium bromide.

3. The method for preparing the heterocyclic aramid nanofiber membrane according to claim 1, characterized in that: The reaction in step (1) is carried out under the protection of inert gas. First, an aromatic heterocyclic diamine monomer containing benzimidazole or benzoxazole and an aromatic diamine monomer are added to a solvent, and the water content in the obtained solution is ≤100ppm; then, an aromatic diacyl chloride monomer is added in two stages for reaction: in the first stage, 70% to 90% of the amount of the aromatic diacyl chloride monomer is added, and the reaction is carried out at 0 to 5°C for 20 to 40 minutes; in the second stage, the remaining aromatic diacyl chloride monomer is added, and the reaction is carried out at 20 to 40°C for 1 to 2 hours. The mass concentration of the obtained heterocyclic aramid solution is 3% to 7%, the dynamic viscosity at room temperature is 300 to 1200 Pa·s, and the intrinsic viscosity is 10 to 20 dL / g.

4. The method for preparing the heterocyclic aramid nanofiber membrane according to claim 1, characterized in that: The small molecule physical cross-linking agent is sulfuric acid, oxalic acid, phosphoric acid or polyphosphoric acid.

5. The method for preparing the heterocyclic aramid nanofiber membrane according to claim 1, characterized in that: The electrospinning process conditions in step (3) are: voltage 18-30 kV, spinning rate 0.1-3 mL / h, distance between the needle and the roller receiving device 5-30 cm, temperature 20-50° C., and relative humidity 30-50%.

6. The method for preparing the heterocyclic aramid nanofiber membrane according to claim 1, characterized in that: In step (4), the alkaline solution is an aqueous solution of an alkaline substance, the alkaline substance is an organic base or an inorganic base, and the pH value of the alkaline solution is 8 to 11; the soaking temperature is 20 to 80° C., and the time is 1 to 24 hours; the normal pressure drying temperature is 50 to 100° C., and the time is 1 to 5 hours; the annealing temperature is 360 to 410° C., and the time is 0.5 to 1 hour.

7. The method for preparing the heterocyclic aramid nanofiber membrane according to claim 1, characterized in that: The diameter of the nanofibers in the heterocyclic aramid nanofiber membrane obtained in step (4) is 120 to 400 nm.

8. A heterocyclic aramid nanofiber membrane, characterized in that: The heterocyclic aramid nanofiber membrane is prepared by the preparation method of any one of claims 1 to 7.

Citation Information

Patent Citations

  • A high-temperature resistant, high-breakdown-strength intrinsic aramid film and its preparation method

    CN113980312B

  • P-aramid fiber and preparation method thereof

    CN110499542A

  • High-temperature-resistant high-breakdown-strength intrinsic aramid film and preparation method thereof

    CN113980312A